Thalamus & Electrical Status Epilepticus in Sleep - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2012)
Researchers at Children's Hospital, Boston, MA, and other centers in the US; Winnipeg, Canada; and Barcelona, Spain compared the prevalence during a 14-year period and the type of early developmental lesions in 147 patients with electrical status epilepticus in sleep (ESES), 100 with prominent sleep-potentiated epileptiform activity (PSPEA) and 47 patients without PSPEA as controls.